La Lúdica y el Aprendizaje Colaborativo como Estrategia Pedagógica para desarrollar la Rítmica Abordando el Método Dalcroze en los Niños(a) del Curso 601 del Colegio La Amistad I.E.D. (2019)
This research begins with the search for information that allows corroborating the problem, and from the delimitation of the aspects to be improved, implement playful-collaborative strategies. At the same time, the pedagogical intervention is supported with elements of the Dalcroze method, where rhythm contributes to the bodily experience of rhythm.